FACILE SYNTHESIS OF FULLY CONJUGATED AMINOPYRAZINE BASED DIAZOBENZENES AND DIAZOAMINOBENZENES WITH ARYLDIAZONIUM SALTS - Karakaya, Idris (Japan Inst Heterocyclic Chemistry, 2022)
Herein, we report the diazotization of aminopyrazine achieved in good to excellent yields using electronically disparate aryldiazonium salts at room temperature. These novel and fully conjugated diazobenzenes and diazoaminobenzenes were characterized utilizing NMR, HRMS, single crystal Xray diffraction, and UV-Vis techniques. Depending on the position of the functional groups substituted on the aryldiazonium salts and their ability to forge hydrogen bonds, these reactions can diverge into two possible pathways to give diazobenzenes or diazoaminobenzenes selectively. Based on the results of UV-Vis spectroscopic analysis, it was determined that the maximum absorbance band of the compounds was between 333 nm and 363 nm due to their interacting pi-pi* transitions. These results are further supported by DFT calculations, showing these molecules exhibit high absorbance.
Keywords: Heterocyclic-Compounds; Pyrazine Derivatives; Antifungal Activity; Azo; Dyes; Antibacterial; Complexes; Ruthenium; Chemistry; Food